The Effect of Work-Life Balance on Employee Performance with Job Satisfaction as a Mediating Variable - Putri, Ajeng Ayu Manggali; Noermijati (Jurnal Kewirausahaan dan Inovasi, 2025)
This study aims to examine the direct and indirect effects of work-life balance on employee performance at Perumda Air Minum Tugu Tirta of Malang City with job satisfaction as a mediating variable. This quantitative explanatory research investigates causal relationships among variables through hypothesis testing. The sample consists of 173 respondents selected using a saturated sampling technique, targeting all permanent employees at the company. Data were collected through a questionnaire and analyzed using Structural Equation Modeling (SEM) in SmartPLS version 4. The results show that work-life balance has a direct, positive, and significant effect on employee performance. In addition, work-life balance also positively and significantly affects job satisfaction, which in turn has a positive and significant effect on employee performance. The findings further indicate that work-life balance indirectly affects employee performance through job satisfaction as a mediating variable.